Influence of Operational Condition on the Performance of Halotolerant Enriched - Activated Sludge System for Treating Medium Salinity Peanut Roasted Wastewater - Rustiana Yuliasni; Nanik Indah Setianingsih; Kukuh Aryo Wicaksono; Nani Harihastuti (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2018)
This research aimed to investigate the influence of operational condition on the performance of halotolerant enriched - activated sludge system for treating high organic wastewater with medium salinity from roasted peanut industry. Roasted peanut wastewater with VLR ranged from 0.268 to 4.7 kg COD/m3.day and Chloride concentration ranged between 1582 - 4392 mg/L was treated continuously for almost 77 days. Two identical reactor with Volume 25 L, namely R1 a conventional Activated Sludge (AS) System and R2, a halotolerant enriched-AS. Both reactors were running with operational condition: HRT (9 h to 46 h) and MLSS (1000-6000 mg/L). Compared to conventional AS system, Halotolerant enriched-Activated sludge system could remove average of 86.7% COD, compared with conventional AS which was 85.7%. Average COD effluent of Halotolerant Enriched-Activated Sludge was also considerably lower, which was 127 mg/L, than conventional AS which was 150 mg/L. Halotolerant enriched-activated sludge also produced less sludge, giving a high F/M ratio (4.9) compared with conventional AS (3.5). In order to make effluent fulfilled stream standard regulation (at central java region COD was<150 mg/L), the favorable operational condition for both reactors would be at VLR 0.268 to 2.03 kg COD, HRT was 25 hours HRT, with MLSS was 2584 – 3956 mg/L and maximum chloride concentration 1920 mg/L.